Experiments on Part Load Performance of Ground Source Variable Refrigerant Flow System in Winter - Yan Lijun; Zhang Xu; Zhao Deyin; Wu Jiachen (Zhileng xuebao)
Based on the measured data of the ground source variable refrigerant flow system (GSVRFS) in the heating season, this research analyzes the variation of hourly system power consumption per square meter, coefficient of performance (COP) of unit and COP of system along with the change of part load ratio (PLR). The results show that the PLR is distributed mainly from 40% to 70%. Hourly power consumption per square meter varies with PLR in concave form. The COPs of the unit and system vs. the system part load ratio are within a convex performance domain.